2022
DOI: 10.3389/fpls.2022.869432
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of 1,8-Cineole Synthase (SgCINS) Gene From the Leaves of Salvia guaranitica Plant

Abstract: Monoterpenes are one of the most common groups belonging to the terpenoid family, with a C10 structure comprising of two isoprene units. Most of monoterpenes are volatile plant compounds, and they act as signaling molecules between plants and the environment, particularly as defensive compounds against herbivores and pathogens. In this study, 1,8-cineole synthase (SgCINS) gene was identified and cloned from the leaves of Salvia guaranitica plant. To examine the role of SgCINS in insect resistance, we transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 59 publications
5
18
0
Order By: Relevance
“…Moldenke (Despinasse et al, 2017;Hurd et al, 2017) (indicated as BPPS in Figure 4). Candidate Mp_12413 from peppermint clustered with 1,8-cineole synthases (labeled as CINS in Figure 4) of several species of the Lamiaceae (Wise et al, 1998;Kampranis et al, 2007;Demissie et al, 2012;Ali et al, 2022).…”
Section: Cloning and Functional Characterization Of Candidate Mtss In...mentioning
confidence: 99%
“…Moldenke (Despinasse et al, 2017;Hurd et al, 2017) (indicated as BPPS in Figure 4). Candidate Mp_12413 from peppermint clustered with 1,8-cineole synthases (labeled as CINS in Figure 4) of several species of the Lamiaceae (Wise et al, 1998;Kampranis et al, 2007;Demissie et al, 2012;Ali et al, 2022).…”
Section: Cloning and Functional Characterization Of Candidate Mtss In...mentioning
confidence: 99%
“…For a rapid survey of terpenoids in transgenic and non-transgenic A. thaliana plant lines, intact leaves of various lines were frozen in liquid nitrogen (LN2), powdered with a ceramic mortar and pestle, and directly inundation in n-hexane as a solvent for 75 h for ensuring complete removal of terpenoids contents as previously described (Ali et al, 2022a;. Approximately 1 µl aliquot of each extract was analysed by the Shimadzu-GC-MS system with three replicates.…”
Section: Terpenoids Extraction and Gc-ms Analysismentioning
confidence: 99%
“…This magnesium cluster binds and interacts with the diphosphate moiety of farnesyl diphosphate (FPP), hence, catalyzing the C15-substrate-FPP formation at the hydrophobic substrate binding pocket (Su-Fang et al, 2014;Abbas et al 2019 andRebecca et al 2020). Eventually, each protein sequence belonging to the terpene synthase family has one or two of these conserved domains (Ali et al, 2017(Ali et al, , 2018(Ali et al, and 2022a. A phylogenetic tree was generated to analyse the evolutionary relationship between SgCMS and other plant sesquiterpene synthase genes, and the evolutionary tree was constructed well by the neighbor-joining method parameters.…”
Section: Overexpression Of Sgcms Gene Altered the Terpene Profiles In...mentioning
confidence: 99%
“…29 Previous studies have demonstrated that transgenic tobacco overexpressing Salvia officinalis 1,8-cineole synthase (SoCINS) enhanced terpenoid production, 30 whereas ectopic expression of Salvia guaranitica (Sg)CINS in transgenic plants can improve resistance against cotton leafworms. 31 Moreover, SoCINS has been found to participate in the regulation of the number and fresh weight of nodules in soybean, suggesting that CINS plays a role in plant development. 32 In the present study, we observed that overexpression of SoCINS in tobacco plants resulted in increased emission of 1,8-cineole and trichome density, leading to a repellent effect on aphids.…”
Section: Introductionmentioning
confidence: 99%
“…1,8‐cineole synthase, a typical multiproduct enzyme in the plant kingdom, is capable of synthesizing the characteristic ‘cineole cassette’ monoterpenes, with 1,8‐cineole as the dominant volatile product in some Nicotiana species 29 . Previous studies have demonstrated that transgenic tobacco overexpressing Salvia officinalis 1,8‐cineole synthase ( SoCINS ) enhanced terpenoid production, 30 whereas ectopic expression of Salvia guaranitica ( Sg ) CINS in transgenic plants can improve resistance against cotton leafworms 31 . Moreover, SoCINS has been found to participate in the regulation of the number and fresh weight of nodules in soybean, suggesting that CINS plays a role in plant development 32 …”
Section: Introductionmentioning
confidence: 99%